2011
DOI: 10.1073/pnas.1110096108
|View full text |Cite
|
Sign up to set email alerts
|

Wing patterning gene redefines the mimetic history ofHeliconiusbutterflies

Abstract: The mimetic butterflies Heliconius erato and Heliconius melpomene have undergone parallel radiations to form a near-identical patchwork of over 20 different wing-pattern races across the Neotropics. Previous molecular phylogenetic work on these radiations has suggested that similar but geographically disjunct color patterns arose multiple times independently in each species. The neutral markers used in these studies, however, can move freely across color pattern boundaries, and therefore might not represent th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
178
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 115 publications
(191 citation statements)
references
References 37 publications
10
178
1
2
Order By: Relevance
“…Artificial butterflies were produced based on wings of Heliconius erato lativitta (Linnaeus) which is found only in the Amazon basin, not in Panama (Brown, 1979; Hines et al , 2011). We calibrated the appearance of the artificial wings to account for bird colour and luminance vision.…”
Section: Methodsmentioning
confidence: 99%
“…Artificial butterflies were produced based on wings of Heliconius erato lativitta (Linnaeus) which is found only in the Amazon basin, not in Panama (Brown, 1979; Hines et al , 2011). We calibrated the appearance of the artificial wings to account for bird colour and luminance vision.…”
Section: Methodsmentioning
confidence: 99%
“…Although Heliconius mimicry rings have become the most widely known mimetic systems due to the variety of shared colour forms found in apparently distantly related species and populations 2,5 , recent analyses suggest that some phenotypes share a common origin within and between species 29 . These recent findings indicate that mimetic races within Heliconius species may be driven in part by shared phylogenetic history in addition to convergent evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations into the phylogeography of several aposematic species have revealed that current or historic barriers to gene flow may impact warning signal diversity (e.g., , Owen et al 1994, Turner & Mallet 1996, Noonan & Gaucher 2006, Hines et al 2011, Gehara et al 2013, Hill et al 2013. Over the course of the late Holocene glacial cycles influenced the biota of northern and tropical regions.…”
Section: Genetic Drift Neutral Forces and Wright's Shifting Balancementioning
confidence: 99%